ANALISIS PENGGUNAAN ALAT PELINDUNG DIRI (APD) COVID-19 PADA PETUGAS PUSKESMAS DI KOTA PADANG - Sari ZA, Ayulia Fardila; Syafrawati, Syafrawati; Fizikriy, Laa Tania (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Introduction: Health workers are groups that are vulnerable to contracting COVID-19. There are 20 health workers in West Sumatra test positive for COVID-19 until April 30th 2020, while six of them are Padang primary health care officers. Using Personal Protective Equipment (PPE) is important to prevent and reduce COVID-19 transmission risk of health workers. This study aimed to measure factors of using PPE for Padang primary health care officers. Methods: Research used a quantitative method with cross sectional design in 12 Padang primary health care from March to July 2020. Independent variables were age, PPE availability, leadership support, knowledge, and attitudes. Dependent variable was PPE usage behavior. Research population was health care officers who directly contacted with people in Padang primary health care area with 100 samples. Primary data collection used questionnaire with accidental sampling technique and analyzed using bivariate analysis. Results:There was a significant relationship between age and PPE usage behavior for health care officers, p value=0.037 (p<0.05). There was no significant relationship among PPE availability (p=0.197), leadership support (p=0.480), knowledge (p=0.936), and attitudes (p=0.747) with PPE usage behavior for primary health care workers. Conclusion:Age factor is related to the use of PPE for Padang public health center officers. Suggested to heads of primary health care to increase workers’ motivation using complete PPE.